Is the Long-Term Use of Benzodiazepines Associated With Worse Cognition Performance in Highly Educated Older Adults? - Liu, Linzi; Jian, Peiying; Zhou, Yifang; Zhou, Jian; Jia, Linna; Tang, Minghui; Zhang, Rongwei; Tang, Yanqing (Frontiers in Psychiatry, 2020)
Background: Benzodiazepines (BZD) are common medications for sedative, hypnotic, and anxiolytic that are especially prevalent in older adults. Previous studies have shown that BZD use could impair users' cognition, significantly affecting their quality of life. Past research has shown that higher education might play a protective role in the process of cognitive decline. Very few studies had examined the cognitive effects of BZD on highly educated older adults. The study aimed to explore how cognitive functions would be affected by benzodiazepines among highly educated older adults. Method: 140 older adults with an average education period of 14.8 years were included in this study. The subjects were divided into three separate groups, the long-term BZD users (≥180 days), short-term BZD users (<180 days), and non-users. Demographics and cognitive assessments for the three groups were analyzed using the analysis of variance (ANOVA), the chi-squared test, and the analysis of covariance (ANCOVA). To examine the association between BZD use and cognition a multiple linear aggression approach was used. Result: All three groups were significantly different from each other when looking at executive functioning in the Trail Making Test B (TMT-B). Compared to the control group, short-term BZD users showed significant defects in TMT-B time (p = 0.002) and TMT-B errors (p < 0.001); long-term BZD users showed significant defect on TMT-B time (p = 0.041). Compared to short-term BZD users, long-term BZD users showed significant merit on TMT-B errors (p = 0.001). No significant differences were found in other cognitive tasks that reflected general cognition, verbal memory, language fluency, and visual memory. After adjusting for demographic, increased BZD use over time was positively associated with scores for the revised Brief Visuospatial Memory Test (r = 0.377, p = 0.012). Conclusion: BZD use may be significantly associated with worse executive functioning in highly educated older adults. However, there is no association between the duration of BZD use and increased cognitive deficits in highly educated older adults. This study identified future experimental directions including potential longitudinal studies, within-subject studies comparing mood disorder patients' cognitive performance before and after onset of BZD use, and between-subject studies that directly compare BZD's effect on subjects with the same baseline of cognitive functioning.